Factors Influencing Nurses in Implementing Documentation of Nursing at Muhammadiyah Hospital, Kediri City - Suhita, Byba Melda; Sutrisno, Joko; Kusumawati, Prima Dewi (Health Notions, 2017)
Documentation in nursing has important role against various kinds of peopleâs demands which are more and more critical and influence peopleâs awareness for their rights from unit of unity. This research aimed at knowing the factors that influenced nurses in implementing the documentation of nursing at Muhammadiyah Hospital, Kediri City,Indonesia. Design of the research was correlational with cross sectional approach. Through simple random sampling technique, it was obtained 78 respondents. Data collection utilized questionnaire and the result of this research was analyzed by utilizing logistic regression. The result of this research showed that most of the respondents had motivation to conduct documentation of nursing in medium category, which were 44 respondents (56.4%), had knowledge in category of sufficient which were 42 respondents (53.8%), and had work stress in medium category, which were 45 respondents (57.7%). In addition, most of respondents had implementation of documentation in category of being not implemented, which were 44 respondents (56.4%). The analysis result of logistic regression showed that the factor of motivation and work stress influenced against the implementation of the documentation of nursing at Muhammadiyah Hospital, Kediri City, East Java Province, Indonesia. In implementing documentation, the factor of motivation and work stress really influenced the nurses in implementing documentation of nursing. In order to increase nurseâs motivation, it needed to conduct control against nurseâs behavior in documenting nursing care, needed to socialize while working in which it was expected to be able to solve a problem from the client.